Meta-Analysis of 13 Genome Scans Reveals Multiple Cleft Lip/Palate Genes with Novel Loci on 9q21 and 2q32-35 (2004)
ABSTRACT: Isolated or non syndromic cleft lip with or without cleft palate (CL/P) is a common birth defect with a complex etiology. A 10-cM genome scan of 388 extended multiplex families with CL/P from seven diverse populations (2,551 genotyped individuals) revealed CL/P genes in six chromosomal regions, including a novel region at 9q21 (heterogeneity LOD score ). In addition, meta-analyses with the addition of results from 186 more [HLOD] p 6.6 families (six populations; 1,033 genotyped individuals) showed genome wide significance for 10 more regions, including another novel region at 2q32-35 ( ). These are the first genome wide significant linkage results P p .0004 ever reported for CL/P, and they represent an unprecedented demonstration of the power of linkage analysis to detect multiple genes simultaneously for a complex disorder.